PENGARUH PEMBERIAN BAWANG PUTIH TERHADAP PENURUNAN KADARKOLESTEROL PADA LANSIA DI PUSKESMAS DELITUA - Siti Marlina naufal (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2020)
Cholesterol is atherogenic or very easy to stick, which then forms plaque on the blood walls. The purpose of this study was to see the effect of garlic on cholesterol levels in the elderly at the Delitua Health Center in 2020. The study design used a group pre-test design test on cholesterol sufferers at the Delitua Health Center in 2020 using a technique of 30 people with purposive sampling technique. Bivariate analysis technique with T test analysis and frequency distribution for univariate (cholesterol levels). The data test method used an observation sheet and a cholesterol level test kit for cholesterol variables. The results of the study: 6 people (50%) had the highest levels of cholesterol before being given garlic, and 1 person (8.3%) had the least 200, and 1 (8.3%) 1 person. , 210 as many as 1 person, after offering garlic the decrease was in the category of 170 (16.7%) as many as 2 people, 179 (16.7%) as many as 2 people, 189 (16.7) as many as 2 people, and the least amount was 169 (8.3%) 1 person, 178 (8.3%) 1 person, 183 (8.3%) 1 person, 188 (8.3%) 1 person, 190 (8.3%) ) as many as 1 person, 198 (8.3%) as many as 1 person. with the results of the T test, 000 shows a p value <0.05 using the SPSS V20.0 application. Conclusion: Based on this, it can be ignored that there is an effect between garlic consumption on reducing cholesterol levels in the elderly. Suggestion: Providing treatment for cholesterol over cholesterol in addition to drugs.